2008
DOI: 10.1126/science.1162369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solid-State NMR Structural Characterization of 13 C-Labeled Graphite Oxide

Abstract: The detailed chemical structure of graphite oxide (GO), a layered material prepared from graphite almost 150 years ago and a precursor to chemically modified graphenes, has not been previously resolved because of the pseudo-random chemical functionalization of each layer, as well as variations in exact composition. Carbon-13 (13C) solid-state nuclear magnetic resonance (SSNMR) spectra of GO for natural abundance 13C have poor signal-to-noise ratios. Approximately 100% 13C-labeled graphite was made and converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
836
1
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,127 publications
(894 citation statements)
references
References 21 publications
38
836
1
7
Order By: Relevance
“…Raman spectroscopy confirmed that the as-grown graphite film was of high quality and highly enriched (99%) in the 13 C isotope ( Supplementary Fig. S1) 18 . As expected, the first-order G-band was observed at 1,518 cm − 1 , while the D-band typically detected at 1,297 cm − 1 was completely absent.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Raman spectroscopy confirmed that the as-grown graphite film was of high quality and highly enriched (99%) in the 13 C isotope ( Supplementary Fig. S1) 18 . As expected, the first-order G-band was observed at 1,518 cm − 1 , while the D-band typically detected at 1,297 cm − 1 was completely absent.…”
Section: Resultsmentioning
confidence: 79%
“…A 13 C-labelled graphite film was grown by CVD of 13 C-enriched methane on Ni foil as described previously 18 . Raman spectroscopy confirmed that the as-grown graphite film was of high quality and highly enriched (99%) in the 13 C isotope ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations